The cold-soaking extract of Chinese yam (Dioscorea opposita Thunb.) protects against erectile dysfunction by ameliorating testicular function in hydrocortisone-induced KDS-Yang rats and in oxidatively damaged TM3 cells. (5th December 2020) - Yu, Shiting; Han, Bing; Bai, Xueyuan; Liu, Shichao; Xing, Xin; Zhao, Daqing; Liu, Meichen; Wang, Siming
Abstract: Ethnopharmacological relevance: Clinical applications and pharmacological research suggest that Dioscorea opposita Thunb. (Chinese yam), a well-known traditional Chinese medicine which has been used for more than 2000 years to nourish kidney-yang and protect the male reproductive system, might be efficacious for the treatment of erectile dysfunction (ED). Aim of the study: This study aimed to investigate the active component extract of Chinese yam, determine its effectiveness in hydrocortisone-induced "kidney-yang deficiency syndrome" (KDS-Yang) rats and in oxidatively damaged TM3 cells and explore the underlying mechanism on restoring erectile function. Materials and methods: We clarified the Chinese yam cold-soaking extract (CYCSE) as the main active extract of Chinese yam by a CCK8 assay and further identified its composition. The KDS-Yang rats were induced by intragastric administration of hydrocortisone. After 10 d of CYCSE intervention, cavernous and testis morphology were stained with hematoxylin and eosin. Inducible nitric oxide synthase (iNOS), cyclic guanosine monophosphate (cGMP), testosterone, 8-hydroxy-2-deoxyguanosine (8-OHdG) and superoxide dismutase (SOD) levels were detected by enzyme-linked immunosorbent assay kits. Leydig cells were performed using immunohistochemistry. Reactive oxygen species were measured using a DCFH-DA fluorescent probe, and testicular collagenous fibers were stained with a Masson kit. Detection of testicular apoptosis was performed by a TUNEL assay. Nrf2 and NQO1 mRNA expression levels were measured by qRT-PCR. The protein expression levels of Nrf2, HO-1, TGF-β1 and SMAD2/3 were analyzed by Western blot. Results: We demonstrated in KDS-Yang rats and oxidatively damaged TM3 cells that CYCSE successfully restored erectile function through ameliorating testicular function. Our data suggested that CYCSE can stimulate the NO/cGMP pathway and restore the cavernous morphology to protect against KDS-Yang-induced ED. It also protected testis morphology, increased Leydig cell proliferation and stimulated testosterone secretion. In the damaged testes, excessive increases in 8-OHdG and inhibition of SOD activity were ameliorated, and the Nrf2/HO-1 signaling pathway was enhanced after treatment with CYCSE, indicating that the antioxidant defense system was activated. These findings were also validated in vitro . Additionally, fibrosis of the testes and TM3 cells was reversed by CYCSE through the TGF-β1/SMAD2/3 pathway. Conclusion: CYCSE has a therapeutic effect on KDS-Yang-induced ED, and the mechanism includes stimulation of testosterone secretion, resistance to oxidative stress and prevention of fibrosis. These findings provide a new scientific verification for the application of Chinese yam in the treatment of KDS-Yang-induced ED. Graphical abstract: Image 1